2008
DOI: 10.1155/2008/578180
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Algorithm: Tasks Scheduling Algorithm for Multiple Processors with Dynamic Reassignment

Abstract: Distributed computing systems [DCSs] offer the potential for improved performance and resource sharing. To make the best use of the computational power available, it is essential to assign the tasks dynamically to that processor whose characteristics are most appropriate for the execution of the tasks in distributed processing system. We have developed a mathematical model for allocating “M” tasks of distributed program to “N” multiple processors (M>N) that minimizes the total cost of the program. Relocatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…By following the same algorithm on the remaining phases final allocation is obtained as present in Table 6 for given example. Overall results also evaluated and compared with algorithm [17] as mentioned in Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By following the same algorithm on the remaining phases final allocation is obtained as present in Table 6 for given example. Overall results also evaluated and compared with algorithm [17] as mentioned in Fig. 3.…”
Section: Methodsmentioning
confidence: 99%
“…A dynamic task allocation method is used here to solve task allocation problem and it allocates the tasks to optimize overall task allocation cost. Some of the other related task allocation methods have been reported in literature such asTask Assignment [1, 10,19], task scheduling [2, 3], Distributed Processing Environment [4], Task Allocation [5,7,9,11,13], data communication in Mobile Computing [6], Dynamic Task Allocation [8], Dynamic Tasks Scheduling [12,16,20,22], Dynamic Optimization Algorithm [14], dynamic programming [15], Dynamic Reassignment [17], Dynamic Load Balancing [18] and Dynamic Task Assignment [21].This research solve here a task allocation problem dynamically in DCS by allocating available processors in such a way that overall load should be balanced so system overloading can be avoided by using the proper utilization of processors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches have been reported for solving the Static tasks assignment problem in a DRTS [1][2][3][4][5][6][7]. While in dynamic allocation a module can be reassigned during program execution [8][9][10][11]. Donight et al [12] has determined the level of reliability of components with expending low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Also it is shown that an optimal dynamic assignment corresponds to a "dynamic" partition imposed by a minimum weight cut in an extended graph. Yadav et al [11] in 2008 developed a mathematical model for multiple processors with dynamic re-assignment. Nagarajan et al [12] in 2010, has developed a model for solving a fuzzy assignment problem using Robust's ranking method.…”
Section: Introductionmentioning
confidence: 99%